2019
DOI: 10.20960/nh.2159
|View full text |Cite
|
Sign up to set email alerts
|

Green tea supplementation improves oxidative stress biomarkers and modulates IL-6 circulating levels in obese women

Abstract: Objetivo: el objetivo de este estudio fue evaluar la prevalencia de hipovitaminosis D en los candidatos a cirugía bariátrica (CB) y su relación con factores de riesgo y los componentes del síndrome metabólico. Material y métodos: los parámetros clínicos, antropométricos y bioquímicos se midieron en 56 pacientes caucásicos incluidos en un protocolo de cirugía bariátrica entre enero y junio de 2014. Los pacientes fueron estratificados en tres grupos de acuerdo al status de vitamina D: suficiencia (≥ 40 ng/ml), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Other studies, such as the one carried out by Noronha et al [ 64 ] on obese women who ingested 450 mg catechin capsules, also showed significant decreases in MDA and IL-6. Spadiene et al [ 65 ] reported that a nutraceutical from Camellia Sinensis L. featuring catechins and other polyphenols produced a decrease in MDA and increase in SOD.…”
Section: Discussionmentioning
confidence: 83%
“…Other studies, such as the one carried out by Noronha et al [ 64 ] on obese women who ingested 450 mg catechin capsules, also showed significant decreases in MDA and IL-6. Spadiene et al [ 65 ] reported that a nutraceutical from Camellia Sinensis L. featuring catechins and other polyphenols produced a decrease in MDA and increase in SOD.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, significant correlations between blood IL-6 levels and MetS constituents have been observed. Research has also demonstrated a positive correlation between IL-6 and T2DM, hypertenon, fasting insulin levels, and BMI ( Noronha et al, 2019 ; Koshino et al, 2022 ). However, because of the limited number of studies, they do not provide conclusive evidence.…”
Section: Discussionmentioning
confidence: 99%